2005
DOI: 10.1177/107110070502600709
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Arthrodesis with a Retrograde Femoral Nail for Charcot Ankle Arthropathy

Abstract: The use of a retrograde femoral nail for ankle arthrodesis in patients with Charcot arthropathy appears to decrease the risk of stress fracture compared with shorter nails without increasing the risk of other complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 13 publications
1
57
0
2
Order By: Relevance
“…Our overall union rate of 79.4% is comparable to the outcomes in that systematic review and the published data we reviewed for the present study (25,79,13,2337) (Table 4). The published data review presented in Table 4 identified 342 diabetic patients with CN who underwent TTCA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our overall union rate of 79.4% is comparable to the outcomes in that systematic review and the published data we reviewed for the present study (25,79,13,2337) (Table 4). The published data review presented in Table 4 identified 342 diabetic patients with CN who underwent TTCA.…”
Section: Discussionsupporting
confidence: 86%
“…The contraindications specific to using the intramedullary nail (IMN) technique include active infection, severe angular deformity of the distal tibia, severe osteoporosis, and an intact subtalar joint (1). TTCA has been used as a method for limb salvage to avoid major amputation, in particular, in diabetic patients with lower extremity complications (29). This technique has gained popularity over the years, in part owing to the increased rigidity of the construct compared with that of other fixation techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While many authors [36][37][38][39][40][41][42] have reported complications in treatment of fractures in diabetic patients, only a small number of studies have reported results in the treatment of non-union in diabetic patients or in non-diabetic patients [43]. The size of our diabetic sample treated with MSCs comprising 86 patients is relatively small, which is a weakness of this study.…”
Section: Discussionmentioning
confidence: 63%
“…[19] Daha uzun bir çivi ile artrodez yapılırsa stres odaklanması ortadan kaldı-rılarak kaynama elde edilir. [20] Bir hastamızda ameliyat sonrası ikinci ayda çivi proksimalinde kırık ortaya çıktı. Bu hastadaki çiviyi daha uzun bir çiviyle değiştirerek hem artrodez sahasında hemde proksimaldeki kırıkta kaynama elde edildi.…”
Section: Discussionunclassified